2018
DOI: 10.1080/14767058.2018.1519544
|View full text |Cite
|
Sign up to set email alerts
|

Association between insurance type and pregnancy outcomes in women diagnosed with hypertensive disorders of pregnancy

Abstract: Medicaid was not associated with a particular hypertensive disorder in pregnancy, yet those with Medicaid experienced more severe BP elevations and higher rates of adverse neonatal outcomes. More research is needed to understand potential risk factors and ways to improve outcomes for those with publicly funded insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Other literature investigating disparities in maternal morbidity by insurance status has been largely limited to comparisons between Medicaid versus privately insured women. The results of the study support the need to focus on the broader range of insurance types (Brandon et al, 2009 ; Greiner et al, 2018 ; Fingar et al, 2018 ; Lipkind et al, 2009 ).…”
Section: Discussionsupporting
confidence: 65%
“…Other literature investigating disparities in maternal morbidity by insurance status has been largely limited to comparisons between Medicaid versus privately insured women. The results of the study support the need to focus on the broader range of insurance types (Brandon et al, 2009 ; Greiner et al, 2018 ; Fingar et al, 2018 ; Lipkind et al, 2009 ).…”
Section: Discussionsupporting
confidence: 65%
“…As reported in previous studies, severe ICP as well as preeclampsia are risk factors of AFOs 19,20 , including preterm delivery, low birth weight, NICU admission, and stillbirth 12,21 . This study found that both planned and unplanned CD cases had increased fetal complications compared to vaginal delivery in ICP patients.…”
Section: Discussionmentioning
confidence: 54%
“…This cross-sectional study on PRAMS data in 26 states found a linear and positive relationship between dental visits during pregnancy and state Medicaid dental coverage for adult pregnant women. Enrollment in Medicaid itself was shown to be a predictor for low health care utilization and poor health outcomes [43][44][45][46][47] as Medicaid beneficiaries share key sociodemographic factors that may impact access to health services. However, Medicaid-enrolled pregnant women may face more significant barriers to accessing dental care.…”
Section: Discussionmentioning
confidence: 99%